'Consumed by breathing' – a critical interpretive meta-synthesis of the qualitative literature. (March 2014) - Harrison, Samantha Louise; Apps, Lindsay; Singh, Sally J; Steiner, Michael C; Morgan, Mike DL; Robertson, Noelle
Objective: To derive an improved understanding of how patients respond to, appraise, and understand the experience of an acute exacerbation of chronic obstructive pulmonary disease via a critical interpretive meta-synthesis. Methods: Search terms – Exacerbate* OR hospital* AND 'Chronic obstructive' OR emphysema OR bronchitis AND interview* OR qualitative. Inclusion criteria – Primary research published in English of patients' experiences of an acute exacerbation of chronic obstructive pulmonary disease. Data extraction and synthesis – eight papers were identified. Data were extracted by three researchers and constructs elicited via reciprocal translational analysis. Findings: Themes reflected two domains of understanding an acute exacerbation: (1) Acute effect – encompassing intense emotions, somatic awareness and patients need for rescue. (2) Sustained regulation – reflecting life as interrupted, ongoing beliefs and behaviour and help-seeking. Discussion: Acute exacerbations of chronic obstructive pulmonary disease result in heightened patient arousal, vigilance and powerlessness in response to symptoms. Ongoing, psychological interventions which promote partnership working by both acknowledging patients fear and shaping their appraisals may mitigate distress, enhancing the impact of health messages and engagement in pulmonary rehabilitation.